ANALISIS INVESTASI SAHAM MENGGUNAKAN ANALISIS FUNDAMENTAL TOPDOWN PENDEKATAN PRICE EARNING RATIO (PER) PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG LISTING DI BURSA EFEK INDONESIA - B31112056, DWI MARIANA (Jurnal Manajemen Update, 2016)
This study aims to determine the intrinsic value contained in a company's stock, in which the studied company is a company incorporated into consumer goods industry sector. This study uses descriptive and fundamental analysis topdown with a price-earnings ratio (PER). The results showed the company's stock thirteenth consumer goods industry sector can be used as an investment destination for investors. Then based on the results of the valuation of stocks with price-earnings ratio (PER), the average company in the consumer goods industry sector in 2012 to 2015 in a state where the intrinsic value is less than the market price (overvalued) and generally companies that have undervalued happens to companies that have assets (small), while companies that have large assets (big) generally in condition overvalued. So the investment decisions that should be done is to buy shares of companies that have assets (small). Keywords: Intrinsic Value, Fundamental Analysis topdown, Price Earning Ratio (PER).